Twister on Tuesday - Osborne, Mary Pope.; Murdocca, Sal. (2001)
Jack and Annie travel back to the Kansas prairie to gain an understanding of how hard life was for the pioneers. They also experience the terror of a tornado.
Ages 6-10
Keywords: Time travel -- Fiction; Frontier and pioneer life -- Kansas -- Fiction; Tornadoes -- Fiction; Tree houses -- Fiction; Kansas -- Fiction; Fiction